Open Innovation Technology Transfer in a Peripheral Region - Gareth Davies (2019 UIIN University-Industry Interaction Conference, 2019)
This paper provides a case study of AgorIP, an initiative to support technology transfer in a post-industrial region through an Open Access Open Innovation approach. Developed in south west Wales the initiative involves academia, health boards and industry, with 234 active projects, of which 89 have reached an outcome. By examining the current portfolio, the study investigates the potential to increase the scale and scope of Technology Transfer activity through an Open Access Open Innovation approach. The portfolio demonstrates a range of sources, characteristics and outcomes which align with the dynamics of the conceptual model described by Bradley, Hayter et al. (2013), including its potential for Open Innovation. Focus on smart specialisations shows interactions between sectors in realising opportunities, suggesting a need to look beyond sector/actor-specific interventions. Alongside growth in the scale and scope of Technology Transfer activity, the involvement of experienced and new Originators and Technology Transfer Officers suggests capacity-building is occurring in both activity and support. The initiative offers both researchers and practitioners an opportunity for further insight to the challenges and opportunities for Open Innovation Technology Transfer in a peripheral region. Expansion of the AgorIP approach into further initiatives, by sector, geography and organisation helps ensure that learning from this instantiation will be of value for further development and delivery of technology transfer activities.